Potensi Dan Pengelolaan Wakaf Uang Untuk Pengentasan Kemiskinan Di Indonesia - Neni Nuraeni; Mia Lasmi Wardiyah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
This study explores the potential and management of cash waqf that can later be projected for poverty alleviation in Indonesia. Cash waqf is considered as one of the potential solutions for poverty alleviation, but its role has yet to be significant. The potential of cash waqf can be maximized through the cooperation of various institutions. The research method used is descriptive-analytical by reviewing various literature and data relevant to the issues raised. The results show that the potential of cash waqf is huge, but the collective awareness of the community still needs to be improved. Managing cash waqf through investment in financial instruments and the real sector is important and has the potential to alleviate poverty. In safeguarding the value of the waqf itself, it can be guaranteed by deposit insurance institutions and sharia insurance. Poverty alleviation can be achieved through collaboration between waqf institutions, the community, and the government, which is a concrete step towards realizing this goal.